(untitled) (Research, Society and Development, 2020)
The influence of metabolizable energy (ME) and methionine plus cystine concentration of the diet on performance the laying hens from 24 to44 weeks of age. The experimental design was completely randomized with 9 treatments in a factorial arrangement with 3 metabolizable energy levels (2755; 2900; and 3045 kcal/kg) and, 3 methionine + cystine digestible levels (0.603%; 0.670%; and 0.737%), evaluated for five periods of 28 days each. For the entire study interaction was observed (P<0.05) for the feed intake, egg production, egg mass conversion, and conversion per dozen eggs. For egg quality was interaction for percentage of shell and yolk and all serological variables. Histomorphometric variables in the small intestine and uterus only there was no interaction with the width of the intestinal villus and uterus. It is recommended to use 0.603% digestible Met+Cys associated with a level of 2900kcal / kg diet of white laying henson ME between 24 and 44 weeks of age.